Biomorphs with memory. Issue 1 (2nd January 2018) - Alonso-Sanz, Ramón
Abstract: An exploratory study is made on the dynamics of discrete maps in the complex plane endowed with memory of past iterations. The study deals with the generalized breakout condition that generates the so called biomorphs, i.e. a kind of Julia sets whose form reminds to that of certain types of living microorganisms.   Metamorphosis of a biomorph with memory of degree alpha Graphical Abstract: